THE EUROPEAN PAEDIATRIC CONGRESS (EUROPAEDIATRICS-2009) (MOSCOW, 3-6 JULY 2009) - A.A. Author ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):151-158)